2019
DOI: 10.3390/ijms20051009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dual Interaction of Natural Rhamnolipids with Plant and Fungal Biomimetic Plasma Membranes through Biophysical Studies

Abstract: Rhamnolipids (RLs) are potential biocontrol agents for crop culture protection. Their mode of action has been proposed as dual, combining plant protection activation and antifungal activities. The present work focuses on the interaction of natural RLs with plant and fungi membrane models at the molecular scale. Representative models were constructed and the interaction with RLs was studied by Fourier transform infrared (FTIR) and deuterium nuclear magnetic resonance (2H NMR) spectroscopic measurements. Molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 98 publications
2
62
0
11
Order By: Relevance
“…Rhamnolipid insertion inside the lipid bilayer does not strongly affect lipid dynamics but the nature of the phytosterols could influence the effect of the glycolipids on plant plasma membrane destabilization. These subtle changes in lipid dynamics could be linked with plant defense induction (Monnier et al, 2019). Interestingly, whereas no receptor for rhamnolipid perception has been identified so far, the mc-3-OH-acyl building block of rhamnolipids is sensed by the lectin S-domain-1 receptor-like kinase LORE (Kutschera et al, 2019; Figure 1).…”
Section: Rhamnolipids Trigger Local Resistance Against Plant Pathogensmentioning
confidence: 99%
“…Rhamnolipid insertion inside the lipid bilayer does not strongly affect lipid dynamics but the nature of the phytosterols could influence the effect of the glycolipids on plant plasma membrane destabilization. These subtle changes in lipid dynamics could be linked with plant defense induction (Monnier et al, 2019). Interestingly, whereas no receptor for rhamnolipid perception has been identified so far, the mc-3-OH-acyl building block of rhamnolipids is sensed by the lectin S-domain-1 receptor-like kinase LORE (Kutschera et al, 2019; Figure 1).…”
Section: Rhamnolipids Trigger Local Resistance Against Plant Pathogensmentioning
confidence: 99%
“…Recently, a combination of biological and biophysical approaches demonstrated that the interaction of synthetic glycolipids with biomimetic PM correlates with the plant biological response [37]. Biophysical studies and molecular modeling simulations showed that rhamnolipids fit into plant PM models but do not significantly affect lipid dynamics [38]. Amphiphilic phyto-oxylipins can also interact with plant biomimetic PM by modifying the lateral organization of domains in a lipid-dependent manner [39].…”
Section: Interaction Of Amphiphilic Elicitors With the Plant Plasma Mmentioning
confidence: 99%
“…Because the lipid composition of a membrane is plant-, tissue-, or even organelle-specific, this information may be scarce but a few examples exist in the literature (see, for instance, References [43][44][45] for A. thaliana). Of course, the closer to the real membrane the lipid composition is, the more it will be biologically relevant, with the important caveat that increased complexity of the model will result in a more complex interpretation of the biophysical data (e.g., Reference [38] for NMR). Hence, it is important to choose the lipid composition with an adequate trade-off between the membrane complexity (and thus biological relevance) and the interpretability of experimental data.…”
Section: Biomimetic Membrane Modelsmentioning
confidence: 99%
“…Given their amphiphilic nature, it was postulated that RLs could interact with plant membrane lipids (Sanchez et al , ). Recently it has been demonstrated that RLs fit into plant lipid‐based membrane models and are located near the lipid phosphate group of the phospholipid bilayers, near phospholipid glycerol backbones (Monnier et al , ). RL insertion inside the lipid bilayer does not strongly affect lipid dynamics but the nature of the phytosterols could influence the effect of RLs on plant plasma membrane destabilization.…”
Section: Introductionmentioning
confidence: 99%
“…RL insertion inside the lipid bilayer does not strongly affect lipid dynamics but the nature of the phytosterols could influence the effect of RLs on plant plasma membrane destabilization. These subtle changes in lipid dynamics could be linked with plant defence induction (Monnier et al , ). Interestingly, synthetic molecules derived from the RL structure are also known to induce plant immunity.…”
Section: Introductionmentioning
confidence: 99%